Liquidity, Debt Policy and Enterprise Risk Management (ERM) On Firm Value: Dividend Policy as A Moderating Variable in Indonesian Consumer Cyclical Companies - Angeline Limangu; Achmad Kautsar (International Journal of Social, Economic, and Business, 2024)
This study aims to examine the effect of liquidity, debt policy, and enterprise risk management (ERM) on firm value with dividend policy as a moderating variable in consumer cyclical sector companies listed on the Indonesia Stock Exchange for the period 2018-2022. The technique used in this sampling is purposive sampling and 25 companies were obtained as samples in this study. The data were analyzed using multiple linear regression and moderated regression analysis (MRA) using modprobe and calculated with SPSS Version 27 software. Research results showed that liquidity proxied by current ratio and debt policy proxied by debt-to-equity ratio have a significant and positive effect on firm value. While enterprise risk management (ERM) has no significant effect on firm value and dividend policy proxied by dividend payout ratio is unable to moderate the effect of liquidity (current ratio) and debt policy (debt to equity ratio) on firm value. Therefore, consumer cyclical sector company needs to carry out effective liquidity management in running its business so that operational activities can generate profits as expected and manage company debt with the right amount to avoid risks that can reduce company value.